KEKUATAN PEMBUKTIAN AKTA DIBAWAH TANGAN JUAL BELI TANAH DAN BANGUNAN YANG BERSERTIFIKAT HAK MILIK: Keywords: Power of Law, Underhand Deed, and Sale and Purchase of Land and Buildings. - Fitriah, Dillah; Rachniatun, Siti; Napisah, Napisah (Program Studi Muamalah Fakultas Syariah dan Hukum, 2023)
This thesis is the result of research on the strength of proof of private deed of sale and purchase of land and buildings with certificates of ownership from the perspective of sharia economic law from a study of court decisions Number: 699/PDT.G/2020/PN.JKT.BRT. Evidence that there has been a sale and purchase of land rights, then it should be that the correct sale and purchase of land rights must be carried out before the Land Deed Making Officer (PPAT). In reality, in people's lives, there are still many buying and selling of land that are carried out without PPAT interference, namely buying and selling with private agreements which are sometimes only evidenced by a receipt and only having proof of ownership of the land which is still in the name of the old owner (seller). With the formulation of the problem 1) What is the strength of the proof of the deed under the hands of the sale and purchase of land and buildings with certificates of ownership based on Court Decision Number: 699/PDT.G/2020/PN.JKT.BRT? 2) What is the review of Sharia Economic Law on the strength of proof of underhanded deeds of buying and selling land and buildings that are certified as property rights based on Court Decision Number: 699/PDT.G/2020/PN.JKT.BRT? The purpose of this research is that the parties who carry out land and building buying and selling transactions are based on statutory regulations and Islamic sharia provisions. The type of research used is library research with a normative legal research approach. The main data source used in this study is secondary data with the method of collecting data from literature and document studies. The data analysis method was carried out using qualitative methods with descriptive analysis. The results of this study indicate that 1) The strength of the proof of the underhanded deed of sale and purchase of land and buildings with certificates of ownership in the decision No. 699/PDT.G/2020/PN.JKT.BRT is valid and has permanent legal force. the legality of the underhanded deed because it has fulfilled the legal requirements of an agreement contained in article 1320 of the Civil Code where the agreement for the sale and purchase of land and buildings does not absolutely have to be with a deed drawn up by the PPAT, has permanent legal force because it has the same evidentiary power as authentic deed. The transfer of land rights with certificates of ownership was resolved by granting the Plaintiff the right to act as the attorney for the Defendant before the appointed Land Deed Making Officer. 2) Review of sharia economic law on the strength of proof of underhand deed in the sale and purchase agreement of land and buildings that are certified with ownership rights in decision Number 699/PDT.G/2020/PN.JKT.BRT is that the contract is valid and has permanent legal force. The validity of the contract in buying and selling is because it has fulfilled the conditions and pillars that have been determined by Islamic law. Permanent legal force because the sale and purchase was carried out in cash which was poured into a sale and purchase agreement then made and signed by the Plaintiff and Defendant. this is in accordance with one of the principles of proof in Islamic law, namely the principle of al-kitabah (written).